Sexism and Gender Bias Against Men in TikTok Comment Sections: A Comparative Study of the “Kampus Cantik” and “Kampus Ganteng” Trends - Afaf Zakiyah Adzra; Ananda Wiratama; Nadya Intan Zahra; Prim Christ Rasya S; Salsabila; Sekar Arum Putri R (SAJMR : Southeast Asian Journal of Management and Research, 2026)
This study aims to examine the forms of discourse, the ways in which society interprets and normalizes them, and the factors contributing to gender bias within the “Kampus Cantik” and “Kampus Ganteng” trends on social media platforms. This qualitative study employed a Critical Discourse Analysis (CDA) approach to uncover the power relations, ideologies, and social representations embedded in users’ commentaries on both trends. Data collection techniques included virtual observation through the examination of user activities and interactions, as well as digital documentation by gathering screenshots of comments, videos, and upload descriptions that served as the objects of analysis. The findings reveal distinct patterns of responses between the “Kampus Cantik” and “Kampus Ganteng” trends. Comments on the “Kampus Cantik” trend were predominantly characterized by appreciation and expressions of female solidarity, whereas the “Kampus Ganteng” trend was largely dominated by teasing and sexually suggestive humor. These differences are influenced by several factors, including social constructions of masculinity, unequal moral interpretations, and media representation. This situation highlights the urgency of gender-sensitive digital literacy to raise public awareness that harassment can be experienced by anyone, regardless of gender. Therefore, digital spaces are expected to evolve into environments that are safer, more equitable, and free from discrimination for all individuals. Keywords: discourse analysis, sexism and the normalization of gender bias, men, comment sections, TikTok.